Evaluation of abdominal expiratory muscle thickness pattern, diaphragmatic excursion, diaphragmatic thickness fraction and lung ultrasound score in critically ill patients and their association with weaning patterns: A prospective study - Priyanka Bansal; Bhawna Jakhar; Rajesh C. Arya; Nidhi S. S. Sultania; Sudha Puhal; Kunal Bansal; Devyani Verma; Aditya Aggarwal; Suresh Singhal (Journal of Anaesthesiology Clinical Pharmacology)
Introduction: Weaning of patient from ventilator and finally extubation is a challenge, especially in critical care setup. Though many parameters are available, based on which, the decision of extubation is taken but still many times, there is failure of weaning. Aim: We conducted a prospective observational study to look for diaphragm and abdominal muscle thickness, contraction, and lung ultrasound as indicator for weaning and extubation. Material and Methods: Patients of either gender aged between 20-50 years, who were on invasive mechanical ventilation for more than 48 hrs. and put on spontaneous breathing trial. A bedside ultrasound examination was performed. Abdominal expiratory muscle thickness, diaphragmatic excursion (DE), diaphragmatic thickness fraction (DTF) and lung ultrasound score (LUS) were measured. Results: 12 patients had simple weaning pattern whereas 5 patients had difficult weaning and 8 patients had prolonged weaning. The mean value of DE was 1.97 cm, DTF- 2.3 mm. The mean value of SOFA score is significant between simple, difficult, prolonged weaning (2.24, 4.56, 7.33 respectively). The DE, which is 2.52, 1.26, 1.81 in simple difficult and prolonged weaning respectively is highly significant. The mean value of LUS was 8.34 and is significant in all weaning patterns. The highest sensitivity is found for SOFA score (84.62) with AUC of 0.88. Conclusion: Evaluation of patient with diaphragm thickness fraction (mean DTF of 26%) and diaphragm excursion (2.52 cm) with mean LUS score of 4.67 opens a new dimension to predict weaning in critically ill patients who are put on spontaneous breathing trial. The sequence of thickness of abdominal expiratory muscles adds to accuracy in successful weaning. Larger muti-center trials are required to make these parameters as a standard practice for weaning patients in critical care setup.